De epidemia à endemia : uma história da dengue em Belo Horizonte (1996-2016) - Huener Silva Gonçalves (2024)
This thesis aims at analyzing the historical trajectory of the Dengue endemic cases spread in Belo Horizonte between the years of 1996 and 2016. Based on the words of Charles Rosenberg in dialogue and contributions from Bruno Latour and Carlos Maia, Dengue has been treated as a framework that allowed the observation of several aspects of human relationships themselves and also those with nature. This mosquito-borne disease was also framed along this path in terms of its epidemiological classification, its public representation, and according to Ludwik Fleck, in the local couplings of the current style of thought. To notions mentioned above, contributions from historiography regarding the role of epidemics and endemics in the processes of building scientific knowledge and public health policies were added. This outline, which is highlighted in chapter 1, cooperated with the examination of the corpus that was made up of sources from the local press and the official and scientific spheres, in order to help to discern the epidemic and endemic phases of the history of dengue in the city. The epidemic phase (1996-2002), focused on chapters 2 and 3, found in the dramaturgy of epidemics, by Charles Rosenberg, an important resource for examining the analyzed crises, under the backdrop of the implementation of the SUS (Unified Health System) and its consequences for vector control. The analysis of sources, coming from newspaper Estado de Minas, indicated the introduction of public representation of dengue in Belo Horizonte from the scenario of the epidemic in Rio de Janeiro in 1986. Content from another newspaper, Hoje em Dia and official sources made it possible to examine the first epidemic of Dengue disease in 1996, in the region of Venda Nova, and in 1998, marked by the first cases and deaths attributed to hemorrhagic Dengue, and by divergences between federative entities regarding their responsibility and by the beginning of the partnership between PBH and UFMG in the combating of the disease. The campaigns were supported by the Aedes aegypti Eradication Plan (PEAa), whose failure in 2002, led to the emergence of the National Dengue Control Program (PNCD). Dengue was already endemic in several regions of Brazil. In Belo Horizonte, official recognition took place in 2003, beginning the endemic phase (2003-2016), which is covered in chapters 4, 5 and 6. Subsidies from Geography and Epidemiology studies made it possible to evaluate how the integrated evolution of natural and social conditions led to the spread of the disease in the city. The process of territorialization of the SUS proved to be important in verifying this situation. Subsidized by contributions from Elisabeth França, Daisy Abreu and Márcia Siqueira’s writings, we evaluated how the coverage curves of local newspapers and the DOM (Official Municipal Register) reacted to the epidemiological curve of the disease in both phases. Furthermore, the endemic phase saw the implementation of regular official campaigns. Research on Dengue fever at UFMG and CPqRR – current IRR – also became regular, an indication of a local branch of the collective thinking about the disease. In 2016, even though it experienced its worst epidemic, the fact that it is an endemic territory, that it has a solid official campaign and scientific tradition for the disease accredited Belo Horizonte to host the Butantan Institute vaccine trials and the Eliminate Dengue: Challenge Brazil project, making it one of the national scientific capitals for the study of Dengue.